1978
DOI: 10.1073/pnas.75.4.1825
|View full text |Cite
|
Sign up to set email alerts
|

Attack of sea urchin eggs by dogfish phagocytes: Model of phagocyte-mediated cellular cytotoxicity

Abstract: To test whether lysosomal degranulation of phagocytes is associated with antibody-dependent cytotoxicity, eggs of Arbacia punctulata were used as targets for blood phagocytes of Mustelus canis. Eggs were coated with heataggregated dogfish IgM and exposed to phagocytes, and cytolysis of eggs was observed by Nomarski optics. Phagocytes adhered, degranulated, and raised fertilization membranes resembling those induced by sperm or ionophore A23187. Lysis was then observed as damage radiating from the point of phag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1979
1979
1998
1998

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…This enzyme is undetectable in dogfish phagocytes (2). Percentage inhibition of catalase release from cytotoxic mixtures paralleled the inhibition of ,B-glucuronidase release shown in Fig.…”
Section: Enzyme Secretion By Phagocytesmentioning
confidence: 72%
See 2 more Smart Citations
“…This enzyme is undetectable in dogfish phagocytes (2). Percentage inhibition of catalase release from cytotoxic mixtures paralleled the inhibition of ,B-glucuronidase release shown in Fig.…”
Section: Enzyme Secretion By Phagocytesmentioning
confidence: 72%
“…We therefore studied whether these agents can inhibit the postphagocytic secretion of lysosomal enzymes from blood phagocytes of M. canis and whether their order of activity in this regard parallels their order of activity in inhibiting phagocyte-mediated cytotoxicity of sea urchin eggs. Because dogfish phagocytes resemble the PMNs of mammals with respect to enzymic equipment (2, 12, 13), response to immunologic (2,12) or nonimmunologic (13) stimulation, and capacity to provoke lysis of appropriate target cells (2), these studies should be relevant to modification of phagocyte-mediated injury in inflammatory states (14).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, in the Port Jackson shark (Heterodontus portusjacksoni), Stokes & Firkin (1971) found that a greater number of yeast were ingested by neutrophils than by eosinophils, with an average of six and two per cell, respectively. Phagocytic cells of the smooth dogfish (Mustelus canis) were found to resemble polyorphonuclear leucocytes (Weissman et al, 1978). In other studies with nurse shark cells, only the neutrophils, not the eosinophils, were reported to be phagocytic (Hyder et al, 1983).…”
Section: Discussionmentioning
confidence: 98%
“…Cells produced by the epigonal and/or Leydig organs may be important in immune responses and in inflammatory processes of elasmobranchs (Fänge & Mattisson, 1981). Studies on phagocytosis by elasmobranch immune cells include both in vivo (Fänge, 1968;Parish et al, 1986b) and in vitro (Weissman et al, 1978;Hyder et al, 1983;Parish et al, 1986a;McKinney & Flajnik, 1997) investigations, but the involvement of cells from the Leydig and epigonal organs has not been examined.…”
Section: Introductionmentioning
confidence: 98%